Dual Tracers of 16α-[18F]fluoro-17β-Estradiol and [18F]fluorodeoxyglucose for Prediction of Progression-Free Survival After Fulvestrant Therapy in Patients With HR+/HER2- Metastatic Breast Cancer - Liu, Cheng; Xu, Xiaoping; Yuan, Huiyu; Zhang, Yongping; Zhang, Yingjian; Song, Shaoli; Yang, Zhongyi (Frontiers in Oncology, 2020)
Objective: The purpose of this study was to employ dual tracers 16α-[18F]fluoro-17β-oestradiol (18F-FES) and [18F]fluorodeoxyglucose (18F-FDG) as imaging biomarkers in predicting progression-free survival (PFS) in ER-positive metastatic breast cancer (MBC) patients receiving fulvestrant therapy. Methods: We retrospectively analyzed thirty-five HR+HER2- MBC patients who underwent 18F-FES and 18F-FDG PET/CT scans prior to fulvestrant therapy in our centre. The SUVmax across all metastatic lesions on the PET/CT were assessed. The heterogeneity of ER expression was assigned by the presence of any 18F-FES negative lesions, for patients with entirely 18F-FES positive lesions were categorized into two groups by the median ratio of FES/FDG SUVmax, low FES/FDG and high FES/FDG. PFS were estimated by the Kaplan-Meier method and compared by the log-rank test. Univariate and multivariate analyses were performed using the Cox proportional hazard model. Results: In total, 12 patients' had both 18F-FES negative and positive lesions, indicating the heterogeneity of ER expression in metastatic lesions. These patients had a low median PFS of 5.5 months (95%CI 2.3-8.7). Of patients with entirely 18F-FES positive lesions, 11 had a low FES/FDG and 12 had a high FES/FDG. These groups had a median PFS of 29.4 months (95%CI 2.3-56.5) and 14.7 months (95%CI 10.9-18.5), respectively. The patients were stratified in three categories based on incorporating both 18F-FES and 18F-FDG imaging results that were significantly correlated with PFS by univariate analysis (P < 0.001) and multivariate analysis (P = 0.006). Conclusion: 18F-FES and 18F-FDG PET could serve as prognostic imaging biomarkers for ER-positive MBC patients treated with fulvestrant therapy.